Systematic review: proton pump inhibitor-associated acuteinterstitial nephritis (2007)
Background: A number of recent case reports and case series suggest that proton pump inhibitors may cause acute interstitial nephritis. Aim: To establish the nature of the relationship (cause or association) between proton pump inhibitor use and development of interstitial nephritis. Methods: Data collection: Two researchers independently searched electronic databases (MEDLINE, EMBASE, GOOGLE, LILACS, COCHRANE) for articles from 1970 to 2006, including all study designs, populations and languages. Two independent reviewers assessed study quality and collected the data. Selection criteria: absence of baseline renal failure, development of interstitial nephritis after proton pump inhibitor exposure, nephritis confirmed by creatinine plus either renal biopsy or recurrence upon reinitiating proton pump inhibitor. Results: Sixty four cases (60% females, mean age 78 years) of proton pump inhibitor-associated interstitial nephritis were found, 60 included in this review (59 confirmed by renal biopsy, one by recurrence upon reinitiating proton pump inhibitor). The most common symptoms were non-specific. The mean proton pump inhibitor treatment duration before diagnosing nephritis was 13 weeks, average recovery time was 35.5 weeks, one patient required permanent dialysis, there were no deaths. Conclusion: Proton pump inhibitor-related interstitial nephritis is rare, idiosyncratic and difficult to predict. It requires a high level of clinical suspicion. While there is not sufficient evidence to establish a causal relationship with certainty, there does appear to be a low-prevalence association.